2010
DOI: 10.5194/bg-7-1159-2010
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis response of daytime net ecosystem exchange during drought

Abstract: Abstract. Continuous measurements of net ecosystem CO 2 exchange (NEE) using the eddy-covariance method were made over an agricultural ecosystem in the southeastern US. During optimum environmental conditions, photosynthetically active radiation (PAR) was the primary driver controlling daytime NEE, accounting for as much as 67 to 89% of the variation in NEE. However, soil water content became the dominant factor limiting the NEE-PAR response during the peak growth stage. NEE was significantly depressed when hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 55 publications
8
32
0
2
Order By: Relevance
“…Furthermore, Körner (1995) and Unsworth et al (2004) found a hysteretic pattern of diurnal NEE which was due to a limitation of photosynthesis caused by stomatal closure at high VPD. Actually, our results are in the same sense as Pingintha et al (2010) who found a VPD saturation value of 12 hPa above which NEE decreased toward constant value when a peanut crop is under water stress condition. Bai et al, (2015) reported that, for cotton, CO2 assimilation increased with increasing VPD, reached the maximum over nearly 31 hPa and then declined.…”
Section: A B C D E Fsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, Körner (1995) and Unsworth et al (2004) found a hysteretic pattern of diurnal NEE which was due to a limitation of photosynthesis caused by stomatal closure at high VPD. Actually, our results are in the same sense as Pingintha et al (2010) who found a VPD saturation value of 12 hPa above which NEE decreased toward constant value when a peanut crop is under water stress condition. Bai et al, (2015) reported that, for cotton, CO2 assimilation increased with increasing VPD, reached the maximum over nearly 31 hPa and then declined.…”
Section: A B C D E Fsupporting
confidence: 79%
“…Since photosynthesis is mainly regulated by light, these results are in general agreement with the relationships found in many other studies (see for example Nieveen et al, 2005), where a saturation value of PAR can be envisaged for the CO2 assimilation. Since the stomatal regulation is strongly influenced by the crop water status, this finding can be explained with the soil water conditions (Pingintha et al, 2010), which in the DS is far from optimum, due to the scarcity of rain in the period May-June 2012 ( Table 2). The soil water scarcity determines the increase of the canopy resistance , which is associated to a decline of the photosynthetic rate (Williams et al, 2001).…”
Section: A B C D E Fmentioning
confidence: 97%
“…In addition, the increasing trend of WUE was found in higher latitude regions, where in contrast to that in lower latitude regions. Recent studies reported that the higher WUE can increase the drought stress experienced by plants by regulating stomatal responses (Cruz et al 2010;Pingintha et al 2010), even through the worsened drought and rising temperature tend to offset this positive effect (Brienen et al 2011). This might imply that the ecosystems in middle and low latitude areas have a weakened effect on resisting an extreme climate event such as drought, while the boreal forest has an enhanced effect on (a) (b) tolerating drought events.…”
Section: Limitation and Implications For Future Ecohydrological Procementioning
confidence: 99%
“…They often demonstrate the impact of anomalies, such as drought (Schwalm et al, 2012), flood (Dušek et al, 2009), and volcanic eruption (Gu et al, 2003). Other studies have analysed responses of CO 2 uptake to different types of radiation (Knohl and Baldocchi, 2008;Niyogi et al, 2004;Oliphant et al, 2011;Urban et al, 2007Urban et al, , 2012, vapour pressure deficit, and temperature (Dewar et al, 1999;Pingintha et al, 2010). There are a few studies based on year-round data sets obtained on a daily basis (Dore et al, 2012).…”
Section: Introductionmentioning
confidence: 99%